Neoplasms and metastasis detection in human blood exhalations with a device composed by nanostructured sensors - Landini, Nicolò; Anania, Gabriele; Fabbri, Barbara; Gaiardo, Andrea; Gherardi, Sandro; Guidi, Vincenzo; Rispoli, Giorgio; Scagliarini, Lucia; Zonta, Giulia; Malagù, Cesare (Sensors and actuators. B, Chemical, 2018)
Colorectal and gastric malignant neoplasms (1) produce tumor markers of various nature (a) that, being vascularized, pollute the blood stream (2). These markers are detected with a device (3) hosting nanostructured chemoresistive sensors (4), by sampling blood specimens from human donors and putting them into the device specimen chamber. A filtered airflow brings the markers released to the sensitive chambers, where sensors reacts to their presence. Sensor responses are then analyzed via statistical methods (i.e. Principal Component Analysis), allowing to identify, in this work, if the specimen is sampled from a healthy or tumor affected donor. [Display omitted] •A device encasing chemoresistive sensors was used to monitor tumor markers.•Different tumor markers are emanated from the blood samples, forming odor patterns.•Single sensor approach showed promising yet modest results with ST25 650 + Au sensor.•PCA approach showed good discrimination between “healthy” and “tumor” populations. Nowadays, the demand for devices capable of efficiently identifying the presence of various biomarkers in human body, connected to a wide variety of pathologies, is progressively increasing. Chemoresistive semiconductor sensors, capable of changing their conductance depending on the chemical reactions between their surface and gaseous analytes, could be a suitable choice for medical devices implementation. In this work, a prototype based on an array of nanostructured sensors was tested, in order to detect the presence of airborne tumor markers in blood samples. These chemicals were conveyed to sensors with an air-flow circuit, equipped with antibacterial filters to maintain the sterility of the system. Resulting signals were acquired, processed and plotted thanks to a custom-made software, realized in Labview®. Statistics on these signals was performed by means of Principal Component Analysis. Both male and female subjects, ranging between 21 to 91 years of age, have accepted to participate in this study, donating their blood samples. Donors were patients affected by colorectal and stomach cancers, at different stages of evolution, and/or having differently localized metastasis, and a healthy control group. The results have shown that the processed sensor responses, well discriminate healthy and tumor affected subjects. Obtained results can be also employed to assess the level of tumor growth and vascularization.